IMPLEMENTASI PENDEKATAN PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) PADA PEMBELAJARAN PKn DI SEKOLAH DASAR - Aziz, Abdul (JPK (Jurnal Pancasila dan Kewarganegaraan), 2018)
This study aims to improve students learning outcomes and learning activities through the implementation of Value Clarification Technique (VCT) learning approach on the fourth grade students' of SD Inpres Pampang I Makassar with PKn subject. The research involved one class as a subject of research given treatment, without a comparison class. Before and after the implementation of VCT, subjects were given a test. The test results were compared to determine the impact of VCT on students learning outcomes. Observations were made on student learning activities. Based on the results of preliminary observations related to PKn subject in SD Inpres Pampang I Makassar, it was revealed that the learning still applies the lecture method, the teacher dominates the learning, while students tend to be passive, they only listen and record the subject matter described by the teacher. Based on the result of the study, it can be concluded that the implementation of VCT learning approach can improve students learning outcomes and learning activities. The implementation of this approach has a positive influence on the ability to convey ideas, established cooperative relationships between teachers and students, the freedom to convey students' feelings related to the solution given to a problem they face and foster student responsibility.